Can Acceptance, Mindfulness, and Self-Compassion Be Learned by Smartphone Apps? A Systematic and Meta-Analytic Review of Randomized Controlled Trials. Issue 4 (July 2020) - Linardon, Jake
Highlights: Examined if acceptance, mindfulness, and self-compassion can be learnt by apps. Twenty-seven trials were examined in a meta-analysis. Apps resulted in small improvements in acceptance, mindfulness, and compassion. Quality of evidence was poor due to many high-risk of bias trials. Abstract: The potential health benefits of acceptance, mindfulness, and self-compassion are well-documented. However, interventions that teach these principles typically rely on face-to-face delivery, which can limit their dissemination. Delivering these interventions through smartphone apps could help overcome this. This meta-analysis examined whether principles of acceptance, mindfulness, and self-compassion can be learned through smartphone apps. Twenty-seven randomized controlled trials were included. Smartphone apps that included acceptance and/or mindfulness components resulted in significantly higher levels of acceptance/mindfulness than comparison conditions ( k  = 33; g  = 0.29; 95% CI = 0.17, 0.41). These effects were moderated by the type of comparison and whether reminders to engage were offered. Smartphone apps also resulted in significantly lower levels of psychological distress than comparisons ( k  = 22; g  = −0.32; 95% CI = −0.48, −0.16). Meta-regression revealed a negative relationship between the effect sizes for mindfulness/acceptance and the effect sizes for distress. Smartphone apps produced significantly greater increases in self-compassion than comparisons ( k  = 9; g  = 0.31; 95% CI = 0.07, 0.56), although the quality of RCTs in this analysis was poor. Findings suggest that principles of acceptance, mindfulness, and self-compassion may be learned through cheap, easily accessible, and low-intensity interventions delivered via smartphone apps. However, the quality of available evidence is poor, as low risk of bias was noted in few trials (18%) and the observed effects were likely explained by a digital placebo.